The Inhomogeneity of Composition Along the Magnetic Cloud Axis - Song, Hongqiang; Hu, Qiang; Cheng, Xin; Zhang, Jie; Li, Leping; Zhao, Ake; Wang, Bing; Zheng, Ruisheng; Chen, Yao (Frontiers in Physics, 2021)
Coronal mass ejections (CMEs) are one of the most energetic explosions in the solar system. It is generally accepted that CMEs result from eruptions of magnetic flux ropes, which are dubbed as magnetic clouds in interplanetary space. The composition (including the ionic charge states and elemental abundances) is determined prior to and/or during CME eruptions in the solar atmosphere, and does not alter during magnetic cloud propagation to 1 AU and beyond. It has been known that the composition is not uniform within a cross section perpendicular to magnetic cloud axis, and the distribution of ionic charge states within a cross section provides us an important clue to investigate the formation and eruption processes of flux ropes due to the freeze-in effect. The flux rope is a three-dimensional magnetic structure intrinsically, and it remains unclear whether the composition is uniform along the flux rope axis as most magnetic clouds are only detected by one spacecraft. In this paper we report a magnetic cloud that was observed by ACE on 1998 March 4–6 and Ulysses on March 24–28 sequentially. At these times, both spacecraft were located around the ecliptic plane, and the latitudinal and longitudinal separations between them were 2.2^° and 5.5^°, respectively. It provides us an excellent opportunity to explore the axial inhomogeneity of flux rope composition, as both spacecraft almost intersected the cloud center at different sites along its axis. Our study shows that the average values of ionic charge states exhibit significant difference along the axis for carbon, and the differences are relatively slight but still obvious for charge states of oxygen and iron, as well as the elemental abundances of iron and helium. Besides the means, the composition profiles within the cloud measured by both spacecraft also exhibit some discrepancies. We conclude that the inhomogeneity of composition exists along the cloud axis.